PROTECTIVE EFFECT OF HONOKIOL AGAINST LPS-INDUCED LUNG INJURY VIA ATTENUATION OF MATRIX METALLOPROTEINASE-9 AND OXIDATIVE STRESS - Li, Hong-Bo; Wang, Lin; Gu, Zheng-Tao; He, Xuan; Su, Lei (Archives of Biological Sciences, 2016)
Despite high morbidity and mortality, no effective options are available for the treatment of acute lung injury (ALI). Therefore, the present study investigated the protective effect of honokiol (HK) on ALI via determination of its effect on several key biomarkers. The results of the study showed that HK significantly inhibited the infiltration of neutrophils and protein leakage induced by lipopolysaccharide (LPS) (p<0.05). The pretreatment with HK considerably boosted the endogenous antioxidant defense system to counteract the oxidative stress in LPS-induced ALI by elevating the levels of superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH). Moreover, the activity of toxic mediators, such as myeloperoxidase (MPO), and lipid peroxidation were significantly inhibited upon treatment with HK. In order to examine the mechanism of action of HK, its effect was quantified using matrix metalloproteinase-9 (MMP-9) activity in bronchoalveolar lavage fluid (BALF) by gelatin zymography. Pretreatment with HK considerably suppressed the activation of MMP-9 in a concentration-dependent manner. These findings suggest that HK protects from lung injury via inhibition of MMP-9, and by enhancing the activity of the endogenous antioxidant defense system. DOI: 10.2298/ABS151020077L Key words: acute lung injury; honokiol; inflammation; MMP-9; oxidative stress Received: October 20, 2015; Revised: November 17, 2015; Accepted: November 18, 2015; Published online: September 9, 2016 How to cite this article: Li HB, Wang L, Gu ZT, He X, Su L. Protective effect of honokiol against LPS-induced lung injury via attenuation of matrix metalloproteinase-9 and oxidative stress. Arch Biol Sci. 2016;68(4):877-81.